Pengaruh Penggunaan Mind Map Terhadap Pemahaman Konsep Pendidikan Agama Islam Bagi Mahasiswa Iain Jember - Suhardi, Andi (IJIT: Indonesian Journal of Islamic Teaching, 2018)
This study examines the effect of mind mapping on the understanding of student concepts in Islamic religious education. Understanding the concept is a form of interpreting, translating an information in the form of objects, activities, abstractions (segregation) as well as events that students have received into semantic memory, then students declare the information using its own way. The problem in this research is whether there is a significant influence of the use of mind map towards understanding the concept in the Islamic education subject. The research method was conducted with quasi experiment with nonequivalent pretest-post test control group design. Hypothesis testing was analyzed using different test (t-test) with 5% significance level. The result of Ho hypothesis testing which states there is no difference of mean score of concept comprehension between student group using mind map with using lecture rejected. The results showed that the significance value of 0.000 is much smaller than the required level of significance of 0.05. It can be concluded that the use of mind map can influence the understanding of the concept of students in Islamic religious education.